Historical Study of Drill Patterns Technique in Acquiring Arabic Language Skill as a Foreign Language - Hamzah, Hamzah (Jurnal Alsinatuna, 2019)
This study aims to explain the drill pattern technique as an old historical technique that still exists and used by foreign language teachers to date. This technique is in fact used as the effective main technique of audio-lingual approach and its variants in learning a foreign language. This research is a qualitative research because it does not touch on the results of nouns or quantity values. As for the type, including library research whose primary data is in the form of qualitative data which sourced from books and literature references relating to the theme under study.The results of this study found that drill patterns techniques in its development lived in two periods, namely during the environmentalist period and the nativist period.